Analisis Implementasi Kurikulum Merdeka Pada Penggabungan Mata Pelajaran IPA dan IPS Kelas 4 Di UPT SD Negeri 31 Gresik - Desy Fatmawati; Iqnatia Alfiansyah; Nanang Khoirul Umam (Jurnal Pendidikan, Bahasa dan Budaya, 2024)
This study aims to determine the implementation and impact of the Independent Curriculum on the combination of grade 4 science and social studies subjects at UPT SD Negeri 31 Gresik in the 2022/2023 academic year. This study uses qualitative research, the research procedure goes through several stages, namely identifying problems, limiting problems, determining research focus, collecting data, processing data, generating theories or hypotheses, reporting research results. Data collection techniques are carried out by means of observation, interviews, documentation. The subjects of this study were school principals, IPAS teachers, and students. The results of the analysis from this study are that the implementation of grade 4 IPAS at UPT SD Negeri 31 Gresik is quite good, CP, TP, teaching modules are implemented quite well, students feel happy with IPAS, although there are still some obstacles in combining science and social studies which are still difficult to combine in one meeting. However, school principals and teachers will continue to learn so that they can implement science subjects even better.